Angiosarcoma in Collision With a Merkel Cell Carcinoma: Case Report and Literature Review. (May 2020) - Hacking, Sean; Chavaria, Hector; Khan, Leonard; Das, Kasturi
Merkel cell carcinoma (MCC) is a rare entity that most commonly arises from the skin. Angiosarcoma (AS) is a rare malignancy with a predilection for elderly males, has endothelial differentiation and a notoriously poor prognosis despite aggressive therapy. Herein, we report an angiosarcoma colliding with a MCC, in a patient with a past medical history of squamous cell carcinoma, status-post radiation therapy. More specifically, our case represents a collision tumor, a rare entity composed of two histologically distinct neoplasms which coincide together at the same location. This case represents the first documented report of such a presentation. With that being said, its clinical course, prognosis, pathogenesis, and molecular profile, currently remains unclear. Importantly, neoplasms are increasingly being found to be associated with radiation therapy, of which our patient had received. Ultimately, however, with the lack of c-MYC immunohistochemical staining, and a short duration between radiation exposure and presentation, the AS in our case was likely coincidental.